2013
DOI: 10.1177/8756087913504581
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of polystyrene/starch blends for packaging applications

Abstract: Polystyrene/thermoplastic starch blends from 90/10 to 50/50 (w/w) were prepared by melt blending. Blends were characterized by scanning electron microscopy (morphology); thermogravimetric analysis (thermal stability and weight content of each component); Fourier transform infrared spectroscopy (identification of functional groups); differential scanning calorimetry (thermal properties); tensile tests (strength, modulus, elongation at break and tenacity) and biodegradation in soil (biodegradability). The biodeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 28 publications
2
26
1
1
Order By: Relevance
“…Standard deviations for these measurements were below 0.3% for all materials. In previous works we found that 70 wt % of neat TPS is biodegraded after 7 days of biodegradation in soil. In this article, the TPS loss after 40 days of biodegradation was in the range of 30–70% depending of the type of nanoclay in the blend.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Standard deviations for these measurements were below 0.3% for all materials. In previous works we found that 70 wt % of neat TPS is biodegraded after 7 days of biodegradation in soil. In this article, the TPS loss after 40 days of biodegradation was in the range of 30–70% depending of the type of nanoclay in the blend.…”
Section: Resultsmentioning
confidence: 77%
“…In the case of the uncompatibilized specimens, an increase in water absorption after clay incorporation was observed. On the other hand, a clear trend of water absorption as a function of clay modification or clay content was not observed, probably because of TPS dissolution or leaching in the water during the test …”
Section: Resultsmentioning
confidence: 92%
“…International Journal of Polymer Science loss W loss , % were estimated for the test specimens as per the following [35]:…”
Section: Degressive Media Exposure Via Soil Burial and Acceleratedmentioning
confidence: 99%
“…Tuy nhiên giá thành của các loại polymer này tương đối cao và khả năng ứng dụng còn thấp. Một hướng nghiên cứu khác là sử dụng các nguồn polymer thiên nhiên như tinh bột, cellulose, chitosan… [3] đưa vào các pha nền polymer thông dụng như PE, PP [4], PS [5,6], PMMA [7]... để góp phần cải thiện khả năng phân hủy bảo vệ môi trường của các polymer này thì trở nên phổ biến hơn.…”
Section: Mở đầUunclassified